Complete Chloroplast Genomes of Acanthochlamys bracteata (China) and Xerophyta (Africa) (Velloziaceae): Comparative Genomics and Phylogenomic Placement - Wanga, Vincent Okelo; Dong, Xiang; Oulo, Millicent Akinyi; Mkala, Elijah Mbandi; Yang, Jia-Xin; Onjalalaina, Guy Eric; Gichua, Moses Kirega; Kirika, Paul Muigai; Gituru, Robert Wahiti; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Plant Science, 2021)
Acanthochlamys P.C. Kao is a Chinese endemic monotypic genus, whereas XerophytaJuss. is a genus endemic to Africa mainland, Arabian Peninsula and Madagascar with ca.70 species. In this recent study, the complete chloroplast genome of Acanthochlamys bracteata was sequenced and its genome structure compared with two African Xerophyta species (Xerophyta spekei and Xerophyta viscosa) present in the NCBI database. The genomes showed a quadripartite structure with their sizes ranging from 153,843 bp to 155,498 bp, having large single-copy (LSC) and small single-copy (SSC) regions divided by a pair of inverted repeats (IR regions). The total number of genes found in A. bracteata, X. spekei and X. viscosa cp genomes are 129, 130, and 132, respectively. About 50, 29, 28 palindromic, forward and reverse repeats and 90, 59, 53 simple sequence repeats (SSRs) were found in the A. bracteata, X. spekei, and X. viscosa cp genome, respectively. Nucleotide diversity analysis in all species was 0.03501, Ka/Ks ratio average score was calculated to be 0.26, and intergeneric K2P value within the Order Pandanales was averaged to be 0.0831. Genomic characterization was undertaken by comparing the genomes of the three species of Velloziaceae and it revealed that the coding regions were more conserved than the non-coding regions. However, key variations were noted mostly at the junctions of IRs/SSC regions. Phylogenetic analysis suggests that A. bracteata species has a closer genetic relationship to the genus Xerophyta. The present study reveals the complete chloroplast genome of A. bracteata and gives a genomic comparative analysis with the African species of Xerophyta. Thus, can be useful in developing DNA markers for use in the study of genetic variabilities and evolutionary studies in Velloziaceae.